Strong elliptic equations of second order in Hilbert space - Laptev, G. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. И. Лаптев. Сильно эллиптические уравнения второго порядка в гильбертовом пространстве G. Laptevas. Stipriai elipsinės antros eilės lygtys Hilberto erdvėje